How to Be 80 Year Old and Have a VO2max of a 35 Year Old - Trine Karlsen; Ingeborg Megård Leinan; Fredrik Hjulstad Bækkerud; Kari Margrethe Lundgren; Atefe Tari; Sigurd Loe Steinshamn; Asbjørn Støylen; Øivind Rognmo (Case Reports in Medicine)
Background. To discuss the cardiovascular and pulmonary physiology and common risk factors of an 80-year-old man with a world record maximal oxygen uptake of 50 mL·kg−1·min−1. Methods. Case report. Results. His maximal oxygen uptake of 3.31 L·min−1, maximal heart rate of 175 beats·min−1, and maximal oxygen pulse of 19 mL·beats−1 are high. He is lean (66.6 kg) and muscular (49% skeletal muscle mass). His echo parameters of mitral flow (left ventricular filling, E = 82 cm·s−1 and E/A = 1.2) were normal for 40- to 60-year-old men. Systolic and diastolic function increased adequately during exercise, with no increase in left ventricular filling pressure. He has excellent pulmonary function (FVC = 4.31 L, FEV1 = 3.41, FEV1/FVC = 0.79, and DLCO = 12.0 Si1) and normal FMD and blood volumes (5.8 L). He has a high level of daily activity (10,900 steps·day−1 and 2:51 hours·day−1 of physical activity) and a lifelong history of physical activity. Conclusion. The man is in excellent cardiopulmonary fitness and is highly physically active. His cardiac and pulmonary functions are above expectations for his age, and his VO2max is comparable to that of an inactive 25-year-old and of a normal, active 35-year-old Norwegian man.